Effect of soil and community factors on the yield and medicinal quality of Artemisia argyi growth at different altitudes of the Funiu mountain - Yang, Di; Liu, Xingqiao; Xu, Xinao; Niu, Tongfei; Ma, Xiaolei; Fu, Guozhan; Song, Chengwei; Hou, Xiaogai (Frontiers in Plant Science, 2024)
Altitude and ecological factors significantly influence plant growth and the accumulation of secondary metabolites.However, current research on the impact of altitude and ecological factors on the yield and medicinal quality of Artemisia argyi (A. argyi) is limited. This study established sampling sites in wild populations of A. argyi across seven altitude ranges on Funiu Mountain. We quantified the yield, output rate of moxa, and key medicinal ingredients.Additionally, we analyzed the response of yield and medicinal quality of wild A. argyi populations to various ecological factors at different altitudes. The results showed that wild populations of A. argyi exhibited higher yields and medicinal quality at altitudes below 500 m. Yield was positively correlated with higher soil total nitrogen (TN) content and lower soil total phosphorus (TP) content, while the improvements in medicinal quality were positively associated with higher population density and lower contents of both soil TN and TP. The variation in soil C/N, C/P, and N/P ratios across different altitudes was substantial, affecting soil mineralization and subsequently influencing the absorption of mineral elements by A. argyi. Notably, the phosphorus content in leaves and stems was negatively correlated with yield and medicinal quality, respectively. In contrast, the accumulation of nitrogen, phosphorus, and potassium in leaves was positively correlated with yield. The differences in the primary medicinal ingredients between the leaves and stems of A. argyi were maximum at altitudes below 500 m. The contents of neochlorogenic acid and cryptochlorogenic acid in both leaves and stems showed a significant positive correlation. In the principal component analysis, the primary medicinal ingredients from the leaves contributed more significantly to the overall quality than those from stems. These results suggest that A. argyi is best suited for cultivation at altitudes below 500 m. Population density and the soil's TN and TP contents play a crucial role in determining the yield and medicinal quality of A. argyi. Futhermore, the medicinal quality of A. argyi is more indicative of the main medicinal ingredients found in the leaves, while the stems also serve as a key organ for accumulating flavonoids and phenolic acids.